Observation and geochemistry of Mn-deposits from the Atlantic coast of the United States - Hathaway, James; Manheim, Frank T (PANGAEA, 1971)
The purpose of the data file presented below is twofold: the first purpose is to make available in printed form the basic data relating to the samples collected as part of the joint U.S. Geological Survey - Woods Hole Oceanographic Institution program of study of the Atlantic continental margin of the United States; the second purpose is to maintain these data in a form that is easily retrievable by modern computer methods. With the data in such form, repeated manual transcription for statistical or similar mathematical treatment becomes unnecessary. Manual plotting of information or derivatives from the information may also be eliminated. Not only is handling of data by the computer considerably faster than manual techniques, but a fruitful source of errors, transcription mistakes, is eliminated.